Development and assessment of an indirect vision training programme for operatory dentistry: Effects on working posture - Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Pugliesi, Priscila Mi Suh [UNESP]; Wajngarten, Danielle [UNESP]; Neves, Tamíris da Costa [UNESP]; Pazos, Júlia Margato [UNESP]; Dovigo, Lívia Nordi [UNESP] (Wiley, 2021)
Objectives: Students experience difficulty working with indirect vision and often adopt inadequate working postures because of it. This study created and then assessed the effects of an indirect vision preclinical training programme on dental students’ working posture. Methods: The study enrolled students in the third year of the 5-year undergraduate programme in dentistry in the School of Dentistry of São Paulo State University (UNESP), Araraquara (N = 54). The programme consisted of four training sessions in which students performed different types of activities in which only a mirror was used to see the procedure they were performing. To evaluate posture, students were asked to perform class III cavity preparations (distal-palatal and mesial-palatal preparations) on upper central and lateral incisors in a dental mannequin (tooth numbers 11, 12, 21 and 22) both before and after the indirect vision training programme. Photographs were taken of the students’ working postures. The photographs were assessed by a duly trained researcher using the Compliance Assessment of Dental Ergonomic Posture Requirements. A descriptive statistical analysis was performed, and the assumptions of normality were verified. Student's paired t test was also performed. The significance level adopted was 5%. Results: A significant difference was found between the percentages of correct ergonomic postures adopted before and after the training programme (p = 0.039). Conclusions: The preclinical training programme for indirect vision was found to have a positive effect on the working postures of the students evaluated herein.
Keywords: ergonomics; occupational diseases; professional education